Syringic Acid Reversed Depression-Resembling Behavior Induced by Chronic Unpredictable Mild Stress Paradigm in Mice (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The aim of the present investigation was to explore the anti-depressive potential of syringic acid in Swiss albino male mice. Mice were exposed to unpredictable stress for 21 sequential days. Imipramine (15 mg/kg, p.o.) and syringic acid (10 and 20 mg/kg, p.o.) were administered for three consecutive weeks to unstressed and stressed mice. Tail suspension test and sucrose preference test were used to evaluate antidepressant potential of the drugs. Syringic acid and imipramine significantly decreased immobility periods of stressed mice as compared to vehicle treated stressed mice in tail suspension test, indicating their antidepressant effects. Syringic acid (20 mg/kg) and imipramine also significantly restored the reduced sucrose preference (%) in stressed mice, which further substantiated their antidepressant effects. Syringic acid and imipramine did not produce significant antidepressant effects in unstressed mice. These drugs did not significantly affect locomotor activity scores of mice. Syringic acid (20 mg/kg) and imipramine significantly reversed chronic unpredictable mild stress (CUMS)-induced increase of plasma nitrite and corticosterone levels; brain malondialdehyde levels and monoamine oxidase (MAO(-A activity. Both the drugs also significantly reversed CUMS-induced decrease in brain reduced glutathione levels and catalase activity. Thus, syringic acid showed significant antidepressant-like activity in mice subjected to CUMS through alleviation of oxidative and nitrosative stress; and inhibition of brain MAO-A activity. Further, antidepressant-like activity of syringic acid in mice subjected to CUMS might also be due to decrease in plasma corticosterone levels. Fig. 1 Illustrates further the scheme of protocol designed with various groups of animals.